Thermally induced rotation of 3d orbital stripes in Pr(Sr0.1Ca0.9)(2)Mn2O7 - Beale, T; Bland, SR; Johnson, R; Hatton, P; Cezar, J; Dhesi, S; Zimmermann, M; Prabhakaran, D; Boothroyd, A (2009)
We have investigated orbital ordering in the bilayer manganite, Pr (Sr0.1 Ca0.9) 2 Mn2 O7, using synchrotron x-ray diffraction techniques, in particular resonant soft x-ray diffraction. Diffraction signals are observed at (0, 1 2, 0) above 300 K and (1 2, 0,0) below 300 K, corresponding to orbital stripes along the a and b axes, respectively. The previously observed transition at 300 K is evidence of a rotation of the orientation of the 3d orbital stripes. Large resonances of the orbital signals are observed at the MnL edges, with a complex dependence on incident photon energy indicative of a weakly Jahn-Teller distorted system. A structural transition observed at 92 K is found not to involve a further change in the orbital order. © 2009 The American Physical Society.